2019
DOI: 10.1242/bio.040352
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis in the scorpion Tityus silvestris: new insights into achiasmatic chromosomes

Abstract: Achiasmatic male meiosis in scorpions is characterized by a high frequency of gaps, asynaptic regions and multivalent associations. Here, we performed an immunocytogenetic analysis to investigate recombination, and synapsis and chromatin-remodeling events during meiosis of the scorpion Tityus silvestris . Our results demonstrate that the synaptonemal complex (SC) begins its organization in the zygotene stage and persists until metaphase I. The advancement of the synaptic process is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Moreover, this is the first study to show the presence of an epigenetic marker in the centromere of an anuran. In other species, H3K27me3 is generally related to facultative heterochromatin, promoting the reversible inactivation of (i) genes presents on the X chromosome 59 ; (ii) repetitive DNA associated with synaptonemal complex organization 60,61 ; (iii) the nonsynapsed autosomal region 24 ; and (iv) the ZW chromatin of birds 26 . DSBs tend not to form in repetitive regions, as they may promote crossing-over in non-allelic regions, generating genomic instability, harmful rearrangements to chromosomal segregation 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this is the first study to show the presence of an epigenetic marker in the centromere of an anuran. In other species, H3K27me3 is generally related to facultative heterochromatin, promoting the reversible inactivation of (i) genes presents on the X chromosome 59 ; (ii) repetitive DNA associated with synaptonemal complex organization 60,61 ; (iii) the nonsynapsed autosomal region 24 ; and (iv) the ZW chromatin of birds 26 . DSBs tend not to form in repetitive regions, as they may promote crossing-over in non-allelic regions, generating genomic instability, harmful rearrangements to chromosomal segregation 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…In these species, changes in the synaptonemal complex (gaps, non-synaptic lateral elements) were observed using ultrastructural microscopy [ 10 ]. Analysis of the behavior of the synaptonemal complex in Tityus and other arthropods can also be inferred by the structural maintenance of chromosome protein 3 (SMC3) immunofluorescence, a component of the cohesins axis that bind to the lateral elements during prophase I [ 13 ]. Despite this, to date, no study has investigated the occurrence of meiotic silencing of unsynapsed chromatin (MSUC) during Tityus prophase I.…”
Section: Introductionmentioning
confidence: 99%
“…Achiasmate meiosis was previously confirmed to be associated only with heterogametic sex in plants, tardigrades, crustaceans, insects, and arachnids or in both gonads (testis and ovary) of some annelids, flatworms, and hermaphroditic mollusks [ 24 ]. Among scorpion species, cytogenetically investigated males showed achiasmatic meiosis [ 10 , 12 , 13 ]. Regarding females, the presence of chiasmata is questionable, most being considered achiasmatic, with only one case of chiasma-like structures in Zabius (Buthidae) [ 8 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in species from other different taxa, particularly insects, have revealed deviations from the well-characterized patterns of the regulation of transcription and MSUC/MSCI displayed by eutherian mammals. For instance, transcriptional activity in grasshoppers, moths, true bugs and scorpions is rather abundant in early stages of meiosis [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Interestingly, many of these species present a sex chromosomal determinism of the type XX for females and X0 for males, which is especially interesting.…”
Section: Introductionmentioning
confidence: 99%